Avaliação microestrutural do aço ASTM A516 grau 60, através de técnicas não destrutivas: ruído magnético Barkhausen (RMB) e correntes parasitas (CP) - Lima Júnior, Joveniano Vieira de (2014)
In this study thirteen samples of ASTM A516 Gr 60, which is a type of carbon steel widely used in the construction of pressure pipes for industrial boilers were selected for microstructural evaluation of the behavior of each sample after a process of thermomechanical treatment. The methods used for this test were nondestructive test: Magnetic Barkhausen Noise (MBN) and Eddy Current (EC) which are electromagnetic techniques with great dependence on the microstructural characteristics of the samples were assessed. The samples were divided into groups and each group underwent a different treatment from others. Two groups of eight samples were cold rolled with a thickness reduction of 1, 3, 5 and 7% and one of the groups was normalized. A sample was as received from the factory, reference sample and the remainder was normalized and then annealing was done at 750 °C. Then all groups were metallographically characterized using an optical microscope to determine the average grain size. After this step signals MBN and EC were collected. The signals were evaluated using signal processing techniques and statistical functions, thereby determining values that correspond to the reflection of thermomechanical treatments on the microstructures. For signs of MBN sought the position and maximum peak amplitude of the signal energy, rms, skewness, kurtosis directed only to the time domain. As for the signs of EC, we sought variations or phase angle and amplitude for different excitation frequencies of the probe. Data were compared with the reference sample, yielding results as expected in the literature